2021
DOI: 10.3390/app12010350
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effectiveness of an Augmented Reality and a Dynamic Simulation System Collaboration in Oil Pump Maintenance

Abstract: The maintenance of oil pumps is a complex task for any operating organization, and for an industrial enterprise in the oil and gas sector of the economy, this issue has a high degree of urgency. One of the reasons for this is a wide spread of pumping equipment in all areas of oil and gas enterprises. At the same time, an aggressive environment, uneven load, remote facilities, and harsh climatic zones (especially in the areas of the Arctic region or production platforms) are factors that make it relevant to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Koteleva et al (2021) studied the effectiveness of the collaboration between AR and dynamic simulation systems in O&G pump maintenance. The system structure and the development of the AR-based system application were designed and tested with Microsoft HoloLens V2 [ 61 ]. It was revealed that the AR + dynamic simulation system optimized the O&G pump’s overall maintenance efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Koteleva et al (2021) studied the effectiveness of the collaboration between AR and dynamic simulation systems in O&G pump maintenance. The system structure and the development of the AR-based system application were designed and tested with Microsoft HoloLens V2 [ 61 ]. It was revealed that the AR + dynamic simulation system optimized the O&G pump’s overall maintenance efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Counteraction to this cannot occur due to isolation, since the energy sector is not able to exist for a long time in isolation from other spheres and external influence [38,39]. As a response to challenges, end-to-end digital technologies and Industry 4.0 technologies are developing [40][41][42][43][44], stimulating the restructuring of the energy sector [45]. Authors have identified seven blocks of technologies, united by common functions or ways of realization: digital and IT, smart grid, renewable and Non-conventional energy sources, storage technologies, and a block of industrial production technologies [46,47].…”
Section: Introductionmentioning
confidence: 99%